Evaluation of Antioxidant and Anti-Inflammatory Activities, and Metabolite Profiling of Selected Medicinal Plants of Nepal - Amit Kumar Shrivastava; Muskan Keshari; Manisha Neupane; Sheshbhan Chaudhary; Purna Kala Dhakal; Laxmi Shrestha; Anjan Palikhey; Chandrajeet Kumar Yadav; Gopal Lamichhane; Mohammad Ujair Shekh; Rakesh Kumar Yadav (Journal of Tropical Medicine, 2023)
This study aimed to evaluate the antioxidant, antiarthritic, and anti-inflammatory properties of extracts from the leaves of twelve different medicinal plants in Nepal. We then evaluated the total phenolic, flavonoid, and tannin contents of the extract using in-vitro assays and characterized it using GC-MS analysis. Results revealed that most of the leaf extracts contained phenolic compounds, flavonoids, tannins, alkaloids, and saponins. Few plants also showed the presence of glycosides, phytate, and vitamin C. Among the studied plants, Neolamarckia cadamba exhibited the highest total phenolic and tannin contents, as 241.53 ± 0.20 µg of gallic acid equivalent/mg and 74.48 ± 1.081 µg of tannic acid equivalent/mg, respectively. Ipomoea batatas exhibited the highest total flavonoid content, as 53.051 ± 1.11 µg of quercetin equivalent/mg. Moreover, Raphanus sativus demonstrated significant ferrous ion chelating, 2,2-diphenyl-1-picrylhydrazyl, hydrogen peroxide scavenging, and total antioxidant activities with IC50 value of 4.76 ± 0.68 µg/mL, 5.84 ± 0.14 µg/mL, 6.89 ± 0.16 µg/mL, and 8.99 ± 0.20 µg/mL, respectively. Similarly, Colocasia esculenta and Cicer arietinum exhibited the highest hydroxyl radical and nitric oxide scavenging activities, measuring IC50 value of 7.22 ± 0.56 µg/mL and 9.06 ± 0.10 µg/mL, respectively. Among all the extracts, Amorphophallus paeoniifolius displayed significant human red blood cell (HRBC) membrane stabilization activity (IC50 = 6.22 ± 0.78 µg/mL). Furthermore, Raphanus sativus, Chenopodium album, Cicer arietinum, and Murraya koenigii exhibited the highest inhibitory activities against protein denaturation with bovine serum albumin, antiarthritic, lipoxygenase inhibitory, and proteinase inhibitory, measuring IC50 of 7.48 ± 0.48 µg/mL, 9.44 ± 1.62 µg/mL, 14.67 ± 1.94 µg/mL, and 28.57 ± 2.39 µg/mL, respectively. In conclusion, this study demonstrated the twelve leaf extracts’ significant antioxidant, antiarthritic, and anti-inflammatory activities.